Strategi Komunikasi Dakwah Melalui Pendekatan Budaya: Studi Kasus di Organisasi Dunia Melayu Dunia Islam (DMDI) - Amiripana Amiripana; Retno Riyaningtyas; Fauziah Fauziah (Fakultas Dakwah dan Komunikasi UIN Sunan Gunung Djati Bandung, 2023)
This study takes the case of a conflict between Malaysia and Indonesia which was caused by a misunderstanding in interpreting information in the mass media. The research was conducted by describing the concept of Malay Tamaddun, the causes of the conflicts that occurred and describing DMDI's efforts in actualizing Malay Tamaddun from the perspective of intercultural communication and da'wah. This study uses a case study method and a qualitative approach with a constructive paradigm. The results of the study show that from a communication perspective, the idea of Tamaddun Melayu initiated by DMDI can be used as a communication message that is carried out to inform, propagate, and influence the public (Malaysian and Indonesian communities) regarding the importance of brotherhood, togetherness, and caring. This is part of efforts to apply intercultural communication, international communication and the concept of cultural diplomacy in reducing conflict. Meanwhile, from the perspective of da'wah, communication based on cultural understanding is part of the da'wah strategy for building harmony through negotiate peace to build a life based on the values of the common good.